2020
DOI: 10.1142/s021797922050201x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and evaluation of speed and lane-changing advisory of CAVS at work zones in heterogeneous traffic flow

Abstract: Emerging connected autonomous vehicle (CAV) technologies provide an opportunity to the vehicle motion control to improve the traffic performance. This study simulated and evaluated the CAV-based speed and lane-changing (LC) control strategies at the expressway work zone in heterogeneous traffic flow. The control strategies of CAV are optimized by the multi-layer control structure based on model predictive control. The heterogeneous traffic flow composed of human-driven vehicles and CAVs is constructed based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Most of the studies however provide only theoretical foundations [22] or show the impact within a simulated environment [23][24][25][26][27][28]. The effects of connected, cooperative, and/or autonomous vehicles are discussed in literature [29][30][31][32]. The main control objective is the work zone throughput.…”
Section: State-of-artmentioning
confidence: 99%
“…Most of the studies however provide only theoretical foundations [22] or show the impact within a simulated environment [23][24][25][26][27][28]. The effects of connected, cooperative, and/or autonomous vehicles are discussed in literature [29][30][31][32]. The main control objective is the work zone throughput.…”
Section: State-of-artmentioning
confidence: 99%
“…Automated vehicles (AVs) have attracted increasing interest in recent years. ey offer a huge potential to improve the operation and safety of transportation systems [12,13]. Studies on AVs' lane changing include two main aspects: lane-changing decision and lane-changing execution.…”
Section: Introductionmentioning
confidence: 99%
“…e results showed that the scheme could effectively reduce the average travel time and pollution emissions. Wu et al [32] established a two-lane lane-changing model and studied the control strategy at the freeway work area under the heterogeneous traffic flow. eir study disclosed that when the CAV penetration rate is high, the combination of the early lane-changing control strategy and the variable speed limits strategy is the optimal choice.…”
Section: Introductionmentioning
confidence: 99%